Pemberdayaan PKK melalui Kegiatan Ekonomi Kreatif Pengolahan Limbah Kulit Jagung - Kikky Vuspitasari, Benedhikta; Niaga Atlantika, Yeremia; Usman, Usman; Beni, Sabinus (Penerbit Goodwood, 2025)
Purpose: Community service activities were carried out in Dharma Bhakti Village, Teriak District, Bengkayang Regency. The team carrying out Community Service activities is a collaboration of lecturers and students from the Entrepreneurship Study Program, totaling 4 lecturers and 3 students as well as 13 PKK women from Dharma Bhakti village. Research methodology: The method of this community service activity is through FGD, lectures and question and answer methods. This community service activity is related to providing material regarding exploiting business opportunities by utilizing local balu materials in the form of corn husks into economically valuable products so that they can improve the economy of the community in Dharma Bhakti Village. Results: Business opportunities for using corn husks can be done by collaborating with the creativity and innovation of PKK women so that they have new opportunities to turn waste into unique products in the form of flowers and key chains. Community service activities in Dharma Bhakti Village are running actively and conducively thanks to the support Dharma Bhakti Village Government. Conclusions: This initiative motivates PKK Dharma Bhakti to innovate for family welfare, promotes environmental awareness through waste processing, and opens new income opportunities from untapped local resources. Limitations: Activity Lack of practicum is a limitation in this activity. Contribution: This activity is able to achieve previously desired.